A note on the inefficiency of technology- and region-specific renewable energy support: The German case - Cosima Jägemann (Institute of Energy Economics at the University of Cologne (EWI), 2014)
Renewable energy (RES-E) support schemes have to meet two requirements in order to lead to a cost-efficient renewable energy mix. First, RES-E support schemes need to expose RES-E producers to the price signal of the wholesale market, which incentivizes investors to account not only for the marginal costs per kWh (MC) but also for the marginal value per kWh (MV el) of renewable energy technologies. Second, RES-E support schemes need to be technology- and region-neutral in their design (rather than technology and region-specific). That is, the financial support may not be bound to a specific technology or a specific region. In Germany, however, wind and solar power generation is currently incentivized via technology- and region-specific feed-in tariffs (FIT), which are coupled with capacity support limits. As such, the current RES-E support scheme in Germany fails to expose wind and solar power producers to the price signal of the wholesale market. Moreover, it is technology- and region-specific in its design, i.e., the support level for each kWh differs between wind and solar power technologies and the location of their deployment (at least for onshore wind power). As a consequence, excess costs occur which are burdened by society. This paper illustrates the economic consequences associated with Germany's technology- and region-specific renewable energy support by applying a linear electricity system optimization model. Overall, excess costs are found to amount to more than 6.6 Bn e2010. These are driven by comparatively high net marginal costs of offshore wind and solar power in comparison to onshore wind power in Germany up to 2020.
Keywords: C61; Q28; Q42; 330; Technology- and region-specific renewable energy support; marginal costs; marginal value